Impact of Rapid Molecular Screening at Hospital Admission on Nosocomial Transmission of Methicillin-Resistant Staphylococcus aureus: Cluster Randomised Trial - Roisin, Sandrine (Public Library of Science, 2014)
DESIGN: Cluster randomised crossover trial with seven wards randomly allocated to intervention or control arm. SETTING: Medical and surgical wards of a university hospital with active MRSA control programme. PARTICIPANTS: All patients hospitalized >48 h in study wards and screened for MRSA on admission and discharge Intervention: Rapid PCR-based screening test for MRSA compared with control screening test by enrichment culture using chromogenic agar. OBJECTIVE: We determined the benefit of PCR-detection versus culture-based detection of MRSA colonisation upon patient admission on early implementation of isolation precautions and reduction of hospital transmission of MRSA. MAIN OUTCOME: Cumulative rate of MRSA hospital acquisition of in patients screened negative on admission. RANDOMIZATION: The sequential order of inclusion of study wards in each arm was randomised by assigning a number to each ward and using a computer generated list of random numbers. FINDINGS: Of 3704 eligible patients, 67.8% were evaluable for the study. Compared with culture, PCR-screening reduced the median test reporting time from admission from 88 to 11 hours (p<0.001) and the median time from admission to isolation from 96 to 25 hours (p<0.001). MRSA acquisition was detected in 36 patients (3.2%) in the control arm and 34 (3.2%) in the intervention arm. The incidence density rate of hospital acquired MRSA was 2.82 and 2.57/1,000 exposed patient-days in the control and intervention arm, respectively (risk ratio 0.91 (95% confidence interval, 0.60–1.39). Poisson regression model adjusted for colonisation pressure, compliance with hand hygiene and antibiotic use indicated a RR 0.99 (95% CI, 0.69 to 1.44). INTERPRETATION: Universal PCR screening for MRSA on admission to medical and surgical wards in an endemic setting shortened the time to implement isolation precautions but did not reduce nosocomial acquisition of MRSA. TRIAL REGISTRATION: clinicaltrials.gov NCT00846105